KEPUASAN KONSUMEN LIPSTIK WARDAH DITINJAU DARI KUALITAS PRODUK, KESADARAN MEREK DAN LABEL HALAL DI SURAKARTA - Wahyu Ardhia Pramesti Warsoedi; Tri Ratna Pamikatsih (Juremi: Jurnal Riset Ekonomi, 2023)
Consumer satisfaction is the level where the needs, desires and expectations of consumers are fulfilled and allows long-term product purchases. This research was conducted to better understand how the influence of product quality, brand awareness and halal labels has an impact on consumer satisfaction. In this study using data collection method by distributing questionnaires with google form, the number of respondents used was 160. The population and sample use the people of Surakarta. In general, multiple linear regression analysis was carried out to analyze the research data. The results showed that product quality and brand awareness had a positive and significant effect on consumer satisfaction, while the halal label had a non-significant positive effect on product quality